Impact of hysterectomy on opioid use in patients with adenomyosis: A nationwide register study - Malin Brunes; Gudny Jonsdottir; Marion Ek; Helena Kopp Kallner; Klara Hasselrot (PLoS ONE, 2025)
Introduction Dysmenorrhea and heavy menstrual bleeding are the most common symptoms in adenomyosis, in addition to infertility and chronic pelvic pain. Hysterectomy is a common treatment for adenomyosis symptoms with curative effect on heavy menstrual bleeding but with less studied effects on pain reduction. Material and methods This is a nationwide retrospective register-based cohort study including all hysterectomized patients with pathology-verified adenomyosis between 1 January 2012 and 31 December 2015 with a long-term follow-up three years pre- and three years postoperatively. Two national registers were linked in order to describe the primary outcome of proportion with use of opioids among hysterectomized patients with and without adenomyosis pre- and postoperatively. Logistic and multinomial regression models were used. Results A total of 2,228 (15%) patients had pathology-verified adenomyosis. Overall opioid use was 18.6% and 21.1% three years before and three years after surgery, respectively. Results showed a significantly increased risk of opioid use three years after hysterectomy in patients with preoperative use of opioids and antidepressants (adjusted Odds Ratio (aOR) 5.7, 95% Confidence Interval (CI) 4.5–7.2 and aOR 1.4, 95% CI 1.1–1.8). The risk of needing long-term opioids was higher among patients with smaller uteri (<300g, aOR 2.8, 95% CI 1.7–4.7) compared to women with uterine sizes ≥600g. Conclusions Hysterectomy does not reduce opioid use among adenomyosis patients in long-term follow-up, although the subjective reduction of pain was not investigated in this study. Women with preoperative use of opioids/antidepressants and uterine size <300g are at increased risk for chronic opioid use.